Payments for agrobiodiversity conservation scaled up in Peru - CGIAR Research Program on Policies, Institutions, and Markets (2019)
Payments for agrobiodiversity conservation services (PACS) provide a mechanism to compensate farmers for conservation of genetic diversity. Following pilot testing by Bioversity International in quinoa, PACS are being scaled up by the Ministry of the Environment to four regions in Peru through a Global Environment Facility program.